2020
DOI: 10.24925/turjaf.v8i12.2533-2540.3592
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Molecular Characterization of ‘Candidatus Phytoplasma Trifolii’, a Member of the Clover Proliferation Grup, Infecting Tomato Plants from Iğdır Province in Turkey

Abstract: The tomato plant exhibiting leaf rolling, witches’ broom, distorted and elongated flower’s sepals in Iğdır province, Turkey, was observed. Total DNA extraction was performed from the symtomatic fresh tomato sample. All DNAs were subjected to Direct and Nested polymerase chain reaction (PCR) with universal primer sets that amplified the 16S rRNA of phytoplasmas. PCR products were purified from agarose gel and cloned into the pGEM T-Easy cloning vector. Recombinant plasmids were introduced into the prokaryotic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…P. australasia' (16SrII-D subgroup) was identified in phytoplasma-symptomatic tomato plants in Turkey, which is the first record nationally (Fig 2). In Turkey, phytoplasmas belong to eight 16Sr groups which are I, IX, and X (Canik et al, 2011(Canik et al, , 2019, II (Ayvaci et al, 2020), V (Sertkaya et al, 2004), VI and XII (Usta and Güller, 2018), and XIV (Çağlar et al, 2013) have been identified in different hosts, including ornamental plants, orchards, weeds, and cultured crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P. australasia' (16SrII-D subgroup) was identified in phytoplasma-symptomatic tomato plants in Turkey, which is the first record nationally (Fig 2). In Turkey, phytoplasmas belong to eight 16Sr groups which are I, IX, and X (Canik et al, 2011(Canik et al, , 2019, II (Ayvaci et al, 2020), V (Sertkaya et al, 2004), VI and XII (Usta and Güller, 2018), and XIV (Çağlar et al, 2013) have been identified in different hosts, including ornamental plants, orchards, weeds, and cultured crops.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-targeting universal primers (R16mF2/R16mR1 for d-PCR and R16F2n/R16R2 for n-PCR) amplifying a segment of 1.8 kb and 1.25 kb, for both steps were adopted as specified by Lee et al, (1993) and Gundersen and Lee (1996), respectively. The reaction parameters and temperature cycles were applied as described by Usta et al, (2018). To ensure the reliability of the PCR assays, DNA of 'Ca.…”
Section: Dna Extraction and Molecular Amplification (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…The sepals of the flowers acquired hypertrophied form, were fused, and created a bell‐shaped sterile bud: phyllody of green or anthocyanin color. The stems of the plants were lignified, and necrosis of the phloem was observed on stem cuts (Khalil et al., ); severe fruit deformation, flower sterility, aerial rooting, purplish leaves and leaf rolling (Usta et al., ); severe dwarfing, yellowing, and decreased flowering (Salas‐Munoz et al., ); stunting, yellowing or purplish leaves, proliferation of laterals buds, hypertrophic calyxes and virescent flowers (Choueiri et al., );…”
Section: Appendix a – Symptoms On Plants Other Than Cydonia Mill Frag...mentioning
confidence: 99%